Membrane Distribution of the Pseudomonas Quinolone Signal Modulates Outer Membrane Vesicle Production in Pseudomonas aeruginosa - Florez, Catalina (mBio, 2017)
The Pseudomonas quinolone signal (PQS) is an important quorum-sensing molecule in Pseudomonas aeruginosa that also mediates its own packaging and transport by stimulating outer membrane vesicle (OMV) formation. Because OMVs have been implicated in many virulence-associated behaviors, it is critical that we understand how they are formed. Our group proposed the bilayer-couple model for OMV biogenesis, where PQS intercalates into the outer membrane, causing expansion of the outer leaflet and consequently inducing curvature. In accordance with the model, we hypothesized that PQS must be transported from the cytoplasm to the outer membrane before it can initiate OMV formation. We initially examined two laboratory strains of P. aeruginosa and found significant strain-dependent differences. PQS export correlated strongly with OMV production, even though equivalent amounts of total PQS were produced by both strains. Interestingly, we discovered that poor OMV producers sequestered the majority of PQS in the inner membrane, which appeared to be the result of early saturation of the export pathway. Further analysis showed that strain-specific PQS export and OMV biogenesis patterns were stable once established but could be significantly altered by changing the growth medium. Finally, we demonstrated that the associations described for laboratory strains also held for three clinical strains. These results suggest that factors controlling the export of PQS dictate OMV biogenesis. This work provides new insight into PQS-controlled virulence in P. aeruginosa and provides important tools to further study signal export and OMV biogenesis.